WOOD STRUCTURE SYSTEM in TRADITIONAL BANJAR HOUSES in INDONESIA - Muhammad Deddy Huzairin; Dila Nadya Andini (Journal of Architectural Research and Education, 2022)
Wood, which is a sustainable material, is widely used for various purposes, including for buildings. The main part of the wooden building lies in the main frame. Wood frame technology is developing quite rapidly, which is generally centered on technology from the Western world. The wood frame technology for traditional houses in Indonesia is unique, which is generally adapted to local conditions, including traditional Banjar houses. Research on traditional Banjar houses has not yet reached an adequate in-depth study of the wooden frame, even though it is unique and responsive to swampland conditions and the local environment. The wooden frame structure and construction system of traditional Banjar houses, apart from adding to the global vocabulary of wooden frames, can also be used as an alternative to wooden frames for conventional buildings. Therefore, this research is important to be carried out. This research was conducted by first taking an inventory of the structural and construction systems of several samples of traditional Banjarese houses, to be analyzed in order to obtain the formulation of the structural and construction system. The existing data and formulations will be combined with the structure and foundation construction that has been obtained in previous studies. A qualitative analysis was also carried out on the obtained formulas to provide an understanding of the forces acting on them and the reactions of the elements and their connections. The method is carried out through secondary data and direct data collection in the field, where the data obtained are compiled and analyzed with a matrix to get the level of regularity of the structure and construction system. The structural and construction systems that have been formulated will be analyzed qualitatively by their actions and reactions in the context of the forces acting on them. It was found that the wooden structure system in a traditional Banjar house consists of 17 structural elements, of which 5 have a major role in the structural system and have unique characteristics compared to other conventional and traditional systems. These structural elements form a solid wooden structural system which is proven by the survival of traditional Banjar houses to this day.